Mental health status and challenges in clinical practice among physiotherapists in the private sector during the COVID-19 pandemic / Nurul Farhana Mohd Haidil ... [et al.] - Mohd Haidil, Nurul Farhana; Danis, Ajau; Majumdar, Anne; Ilias, Kartini (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
The covid-19 pandemic exposed healthcare workers, including physiotherapists, to mental health issues such as stress, anxiety, and depression in the private sector. In minimising the infection risk, they faced challenges operating their rehabilitation facility. This study aimed to identify the mental health status and challenges experienced by physiotherapists in private practice during the Covid19 pandemic. The study setting for this cross-sectional research was conducted at Kuala Lumpur and Selangor, Malaysia. Data were analysed using SPSS 20.0 and described descriptively. A total of 80 private physiotherapists participated in the survey. Statistically, 82.5% of the respondents were females aged 22 and 56 (27.60 ± 5.073). They mostly worked in private organisations (86.3%), especially in Selangor (70.0%). About 61.3% of respondents experienced stress subjectively, and 71.3% and 83.8% had normal anxiety and depression levels, respectively. In clinical settings challenges, 70 (87.5%) respondents recorded that the most challenging was abiding by the healthcare policies were frequent sanitisation for modalities, plinths, and chairs. About 52.5% of participants faced challenges in applying social distancing due to lacking clinic spaces. About 48.4% of physiotherapists experienced decreased income. Additionally, 77.5% of respondents had difficulty applying physical examinations while using telerehabilitation. In conclusion, most physiotherapists in the private sector in Malaysia experience common psychological issues, such as depression and anxiety, except for stress.